Oral rehabilitation in a patient with special needs - Derceli, Juliana Dos Reis; Pinelli, Lígia Antunes Pereira; Giro, Elisa Maria Aparecida; Cabrini, Juliana; Castanharo, Sabrina Maria; Fais, Laiza Maria Grassi (Faculdade São Leopoldo Mandic, 2015)
Cerebral palsy is a disorder caused by central nervous system injuries that can occur during the prenatal, perinatal, or postnatal periods. It is characterized by multiple abnormalities, including impairment of speech, body and motor coordination, balance, intelligence, mastication, and swallowing. Due to abnormal movements of the facial muscles, compounded by impairment of the self-cleansing mechanism of the oral cavity, patients with this condition can develop oral diseases such as caries, periodontal disease, and tooth loss. The aim of this paper is to report a case of a patient with cerebral palsy who presented with absence of the maxillary central incisors, removable prosthesis wear, and oral candidiasis. Impressions of the upper and lower arches and periapical radiographs were obtained. The lateral incisors were found to exhibit root resorption, which contraindicated their use as abutment teeth for fixed prosthodontics. In view of the patient's socioeconomic status and cerebral palsy-related limitations, a resin-bonded fixed partial denture was fabricated and nystatin solution was used for treatment of oral candidiasis. The patient had an esthetically and functionally adequate outcome.

A paralisia cerebral é uma anormalidade causada por lesões no sistema nervoso central que podem ocorrer durante o período pré, peri ou pós-natal. É caracterizada por alterações múltiplas como o comprometimento da fala, da coordenação motora e corporal, do equilíbrio, do intelecto e da mastigação e deglutição. Devido aos movimentos anormais da musculatura facial, juntamente com o comprometimento da função de autolimpeza, o paciente pode apresentar quadros de patologia bucal como a cárie, a doença periodontal e a perda dental. O objetivo deste trabalho foi relatar o caso clínico de um paciente portador de paralisia cerebral com ausência dos incisivos centrais superiores, portador de prótese removível e com um quadro de candidose bucal. Foi realizada a moldagem dos arcos superior e inferior e as radiografias periapicais. Pôde-se observar que os incisivos laterais apresentavam reabsorção radicular, o que contra indicava a sua utilização como pilares para prótese fixa. Devido às condições sócio-econômicas e limitações relacionadas a paralisia cerebral, foi confeccionada uma prótese adesiva e, para a candidose bucal foi instituído o tratamento com solução de Nistatina. O resultado do tratamento foi estética e funcionalmente adequado para o paciente.
Tratamento reabilitador em paciente especiaL
Keywords: Cerebral palsy; Oral candidiasis; Oral rehabilitation; Paralisia cerebral; Candidíase bucal; Reabilitação bucal